Exploring the Score Equivalence of the English and Chinese Versions of the Brief Assessment Scale for Caregivers. (April 2020) - Yang, Grace Meijuan; Hui-Shan Neo, Shirlyn; Teo, Irene; Lee, Geok Ling; Thumboo, Julian; Chia, John; Lau, Annie; Koh, Audrey; Qu, Debra; Che, William Wai Lam; Wee, Hwee Lin; Glajchen, Myra; et al.
Background: Multilingual outcome measures are used so that research studies are more generalizable across language contexts. Objective: To determine the score equivalence of the English and Chinese versions of Brief Assessment Scale for Caregivers (BASC) in Singapore. Method: Caregivers of patients with advanced cancer completed the BASC in either English or Chinese. Multivariable linear regression analysis was used to compare the mean BASC total and factor scores between the 2 language versions, with adjustment for possible confounding variables. Equivalence was declared if the 90% confidence interval of the mean scores fell entirely within an equivalence zone of ±0.5 standard deviation. Results: There were 521 ethnic Chinese participants, of whom 214 answered the English version and 307 answered the Chinese version. The BASC total and factor scores met the criteria for equivalence. Cronbach α coefficients were similar and exploratory factor analysis showed similar 2-factor structures for both language versions. Conclusion: The English and Chinese versions of the BASC were found to be equivalent in terms of similar adjusted mean scores, Cronbach α, and factor structures.